Impact of enhanced ultraviolet-B radiation on flower, pollen, and nectar production - Sampson,B.J.; Cane, J. H. (American Journal of Botany, 1999)
Intensified ultraviolet-B radiation or UV-B (wavelengths between 280 and 320 nm) can delay flowering and diminish lifetime flower production in a few plants. Here we studied the effects of enhanced UV-B on floral traits crucial to pollination and pollinator reproduction. We observed simultaneous flowering responses of a new crop plant, Limnanthes alba (Limnathaceae), and a wildflower Phacelia campanularia (Hydrophyllaceae), to five lifetime UV-B dosages ranging between 2.74 and 15.93 kJ.m(-2).d(-1), Floral traits known to link plant pollination with bee host preference, host fidelity and larval development were measured. Intensified UV-B had no overall effect on nectar and pollen production of L. alba and P. campanularia flowers. A quadratic relationship between UV-B and nectar sugar production occurred in P. campanularia and showed that even subambient UV-B dosages can be deleterious for a floral trait. Other floral responses to UV-B were more dramatic and idiosyncratic. As UV-B dosage increased, L. alba plants were less likely to flower, but suffered no delays in flowering or reductions to lifetime flower production for those that did Bower. Conversely, an equal proportion of P. campanularia plants flowered under all UV-B treatments, but these same plants experienced delayed onset to bloom and produced fewer flowers at greater UV-B intensities. Therefore, intensified UV-B elicits idiosyncratic responses in flowering phenology and flower production from these two annual plants. Diurnal patterns in nectar and pollen production strongly coincided with fluctuating humidity and only weakly with UV-B dosage. Overall, our results indicated that intensified UVB can alter some flowering traits that impinge upon plant competition for pollinator services, as well as plant and pollinator reproductive success
Keywords: CLIMATE; COMPETITION; FLORAL DISPLAY; FLORAL REWARDS-NECTAR; FLORAL REWARDS-POLLEN; FLORAL TRAITS; FLORAL TRAITS-SIZE; FLOWER NUMBER; FLOWERING; HUMIDITY; HYDROPHYLLACEAE; NECTAR SECRETION; OSMIA; PHENOLOGY; POLLEN; POLLEN PRODUCTION; POLLINATION; POLLINATOR; REPRODUCTION; SUGAR; ULTRAVIOLET; WEATHER

Biological impediments to measures of competition among introduced honey bees and desert bees (Hymenoptera: Apiformes) - Minckley,R.L.; Cane, J. H.; Kervin,L.; Yanega,D. (Journal of the Kansas Entomological Society, 2003)
Foraging behaviors, host plant breadth, and agilities of social and solitary bee species differ dramatically. We illustrate how these phenomena can obscure the effects of floral resource competition from our studies on a species-rich, native bee fauna that visit the flowers of creosote bush [Larrea tridentata Coville (Zygophyllaceae)], a widespread dominant perennial plant species in the warm deserts of North America. The potential for competition among the solitary bees that visit creosote bush and honey bees was investigated by two methods: one that is widely used asks if solitary bee abundance and species diversity is less at sites with greater honey bee abundance; and a second. more novel approach that asks if pollen availability is limiting at sites with high bee biomass. We found no relationship among number of honey bees at sited and species richness and abundance of all native bees combined or of Pollen specialist species considered alone. Protein represented in the pollen of the primary host plant greatly exceeded the biomass of bees present at a site. We suggest bee populations are rarely pollen limited in this system or that competition, when it occurs, is highly episodic. Future studies of bee competition will need to assess long-term Population variation among solitary and introduced bees in habitats where floral resources can be measured for multiple flowering plant species, and where bee colony/nest dynamics can be documented, Studies of bee faunas in temperate areas are needed. This paper demonstrates some of the possible pitfalls for studies of competition among highly eusocial and solitary bees, We conclude that basic data (in bee biology and population dynamics are needed before these questions can be satisfactorily answered and, at present, little hard data are available to evaluate the competing hypotheses
Keywords: APIS; Apoidea; BEHAVIOR; COMPETITION; DIVERSITY; FLOWERING; GUILD; HABITAT; LARREA; METHODS; POLLEN; PROTEIN; RESOURCE LIMITATION; VARIATION